The Truth about Small Towns : Poems - Baker, David, 1954- (Book collections on Project MUSE., 1998)
Regional in the best sense, Baker's poems capture the universal human commerce of love and conflict enduring under the water towers and storefronts of America's heartland. Working in syllabics, sonnets, couplets, and free verse, Baker can write unflinchingly about love, illness, madness, and perseverance.